CAN ARGUMENT-DRIVEN INQUIRY MODELS HAVE IMPACT ON CRITICAL THINKING SKILLS FOR STUDENTS WITH DIFFERENT PERSONALITY TYPES? - Undang Rosidin; Nina Kadaritna; Neni Hasnunidah (Jurnal Cakrawala Pendidikan, 2019)
Critical thinking skills are important in the context of 21st-century learning, where students are able to express reasons that support the assumptions or conclusions they obtain. A preliminary study at 25 Bandar Lampung Middle Schools found that science learning had not been maximized in training critical thinking skills. This study aims to determine the effect of applying the Argument-Driven Inquiry (ADI) learning model on students' critical thinking skills based on differences in academic abilities, gender, and personality type. This study used Nonequivalent (Pretest and Posttest) Control Group Design and One-Group Pretest-Posttest Design. The data of pretest and posttest essay questions results analyzed using nonparametric statistical tests. The results showed that there was an effect of ADI learning on critical thinking skills in high and low academic students. Moreover, this model provided a greater influence on students' high academic abilities. The ADI model could also accommodate all male and female students with various types of personality types because the gender and personality type aspects do not show significant differences in students' critical thinking abilities, both between male and female students and students with different personality types. Overall, the ADI model is effective in improving students' critical thinking skills.